Perceived Value and Intention to Revisit Nglanggeran Tourism Village, Special Region of Yogyakarta - Islami, Fitrah Sari; Prasetyo, Andreas Yogi; Simamora, Alex Johanes (Journal La Bisecoman, 2024)
This study aims to examine the perceived value of tourists on their intention to revisit Nglanggeran Tourism Village. Perceived value consists of emotional value, social value, value for money, and cultural value. The object of the study is Nglanggeran Tourism Village, and the subjects are 398 tourists who visited the village. The research variables were measured using a questionnaire on a 5-point Likert scale. Data analysis was conducted using path analysis through structural equation modeling. Based on the data analysis results, emotional value, social value, value for money, and cultural value all influence the intention to revisit Nglanggeran Tourism Village. These findings indicate that tourists' evaluations of the emotions experienced, their connection and bond with the local community, the adequacy of the tourism services relative to the money spent, and the meaningful cultural experiences create positive emotions for the tourists, thus fostering their intention to revisit Nglanggeran Tourism Village. This research contributes evidence, particularly regarding cultural value, in the context of Nglanggeran Tourism Village, enriching the explanation of attitude theory in the context of tourism villages.